Emergence of novel porcine circovirus 2d strains in Thailand, 2019–2020 - Chaitawat Sirisereewan; Thanh Che Nguyen; Taveesak Janetanakit; Roongtham Kedkovid; Roongtham Kedkovid; Roongroje Thanawongnuwech; Roongroje Thanawongnuwech (Frontiers in Veterinary Science, 2023)
Porcine circovirus 2 (PCV2) has been recognized as a causative agent of porcine circovirus diseases (PCVDs) affecting the global swine industry. In this study, the genetic diversity of PCV2 strains circulating in Thailand between 2019 and 2020 was investigated using 742 swine clinical samples from 145 farms. The results showed PCV2-positive rates of 54.2% (402/742) and 81.4% (118/145) at the sample and farm levels, respectively. Genetic analysis of 51 Thai PCV2 genomic sequences showed that 84.3% (43/51) was PCV2d, 13.7% (7/51) was PCV2b and 1.9% (1/51) was PCV2b/2d recombinant virus. Surprisingly, the majority of the Thai PCV2d sequences from this study (69.77%, 30/43) formed a novel cluster on a phylogenetic tree and contained a unique 133HDAM136 on the ORF2 deduced amino acid sequence, which is in one of the previously identified immunoreactive domains strongly involved in virus neutralization. The PCV2b/2d recombinant virus also carried 133HDAM136. The emergence of the novel PCV2d strains predominating in Thailand was discussed. This study highlights the need for further investigations on the spreading of these PCV2d strains in other regions and the efficacy of current commercial vaccines.